Effectiveness of prophylactic antibacterial drugs for patients with liver cirrhosis and upper gastrointestinal bleeding: a systematic review and meta-analysis - Wang, Zhuo; Hu, Han-Shuo; Zhao, Li-Mei; Li, Yu; Liu, Xiao-Dong (Frontiers in Pharmacology, 2024)
Background: Prophylactic antibacterial drugs are used for patients with liver cirrhosis and upper gastrointestinal bleeding, and independent studies have concluded that they can decrease the rate of infection, mortality, and rebleeding in these diseases. However, no comprehensive assessment of this effect has been reported in recent years and available data pertaining to the prognostic implications of diverse categories of antibiotic prophylaxis in individuals afflicted with cirrhosis are notably limited. The objective of this article is to assess the clinical effectiveness of prophylactic antibacterial drugs for patients with liver cirrhosis and upper gastrointestinal bleeding. Methods: Relevant randomized controlled studies and cohort studies which examined the value of prophylactic antibacterial drugs for patients with liver cirrhosis and upper gastrointestinal bleeding were retrieved via Cochrane Library, EMBASE, MedLine, and Web of Science. The search period was from database inception until 30 April 2023. Summing up the relevant data, the dichotomous variable was statistically analysed using the relative risk (RR) value and its 95% confidence interval (CI) and the continuous variable using the mean difference (MD) value and its 95% CI. All analyses were performed using Revman 5.4 software. The study has been registered on the PROSPERO website under registration number CRD42022343352. Results: Twenty-six studies (18 RCTs and 8 cohort studies, including 13,670 participants) were included to evaluate the effect of antibacterial prophylaxis versus no antibacterial prophylaxis or placebo. Prophylactic antibiotics reduced mortality rates (RR 0.66, 95% CI 0.51–0.83), infection rates (RR 0.41, 95% CI 0.35–0.49), rebleeding rates (RR 0.42, 95% CI 0.31–0.56), and length of hospital stay (MD −5.29, 95% CI −7.53, −3.04). Subgroup analysis revealed that the prophylactic administration of quinolone antimicrobials demonstrated the most favorable efficacy, followed by cephalosporins. Both interventions were effective in averting infections frequently observed in patients with liver cirrhosis and upper gastrointestinal bleeding. Conclusion: Based on our investigation, the prophylactic antibacterial drugs confers noteworthy advantages in patients afflicted by liver cirrhosis with upper gastrointestinal bleeding. It has been associated with reductions in mortality, infection incidence, rebleeding occurrences, and the duration of hospitalization. Among prophylactic antibacterial options, quinolones emerged as the foremost choice, with cephalosporins ranking closely thereafter. Systematic Review Registration: https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42022343352, identifier CRD42022343352.